The Blossom Festival : (A Novel) - Coates, Lawrence, 1956- (Book collections on Project MUSE., 1999)
A novel on the orchard country of pre-World War II California with its festivals. It follows the lives of a number of families, including that of an American-born Japanese girl as she tries to fit in, unaware of what awaits her.